Relook at lipoprotein (A): Independent risk factor of coronary artery disease in North Indian population - Yusuf, Jamal; Yadav, Neeraj; Mukhopadhyay, Saibal; Goyal, Abhishek; Mehta, Vimal; Trehan, Vijay; Tyagi, Sanjay (Indian heart journal, 2014)
Lipoprotein (a) [Lp(a)] levels have shown wide ethnic variations. Sparse data on mean Lp(a) levels, its link with clinical variables and severity of coronary artery disease (CAD) in North Indian population needed further studies. 150 patients, each of single vessel disease (SVD), double vessel disease (DVD) and triple vessel disease (TVD) with 150 healthy controls were drawn for the study. Serum Lp(a) estimation was performed by immunoturbidimetric method. Lp(a) had a skewed distribution. Median Lp(a) level was significantly raised in cases as compared to controls (median 30.30 vs. 20 mg/dl, p < 0.001). Cases with acute coronary syndrome (ACS, 55.8%) had significantly higher median Lp(a) levels as compared to those with chronic stable angina (35.4 mg/dl vs. 23 mg/dl, p < 0.001). Significant difference in median Lp(a) levels were observed in patients with DVD or TVD versus control (30, 39.05 vs 20 mg/dl, p < 0.008). Lp(a) level was found to be an independent risk factor for CAD (AORadjusted odds ratio 1.018, 95% CI 1.010–1.027; p < 0.001). Analysis using Lp(a) as categorical variable showed that progressive increase in Lp(a) concentration was associated with increased risk of CAD [AOR from lowest to highest quartile (1, 1.04, 1.43 and 2.65, p value for trend = 0.00026)]. Multivariably AOR of CAD for subjects with Lp(a) in the highest quartile (above 40 mg/dl) compared to those with Lp(a) ≤40 mg/dl was 2.308 (95% CI 1.465–3.636, p < 0.001). Lp(a) above 40 mg/dl (corresponding to 75th percentile)assessed by an isoform insensitive assay is an independent risk factor for CAD. Raised Lp(a) level is also associated with increased risk of ACS and multivessel CAD.